Myocardial work analysis in left ventricular non-compaction, and its association with cardiovascular outcomes. (25th November 2020) - Anwer, S; Heiniger, P.S; Rebellius, L; Schoenenberger-Berzins, R; Kuzo, N; Guastafierro, F; Erhart, L; Gregr, P; Schmid, D; Kindler, C; Gruner, C; Tanner, F.C
Abstract: Introduction: Left ventricular (LV) non-compaction (LVNC) is a rare cardiomyopathy characterised by a two-layered LV myocardium with prominent trabeculae separated by deep recesses perfused from the LV cavity. Myocardial work analysis (MWA) is a novel echocardiographic method that calculates pressure-strain loops from longitudinal strain and bedside blood pressure measurement. Our study investigates the MWA features of LVNC patients and their association with outcomes. Methods: We compared 40 LVNC with preserved LVEF (≥50%) (pEF-LVNC) and 40 LVNC patients with reduced LVEF (<50%) (rEF-LVNC) to 40 healthy matched controls. GE EchoPAC® (Version 203) was used for echocardiographic analysis. A combined endpoint was defined as heart failure progression, sustained ventricular tachycardia, thromboembolic accidents, and atrial fibrillation. Results: Clinical characteristics, conventional echocardiography, and strain analysis results are detailed in Table 1 and Figure 1. Myocardial work index was significantly reduced in rEF-LVNC (1088 [138–1211 mm.Hg%]) and pEF-LVNC (1394 [1138–1501 mm.Hg%]) in comparison to control (1827 [1758–1981 mm.Hg%]), but there was no difference between the two LVNC groups. Global constructive work (GCW) was significantly lower in rEF-LVNC (1094 [947–1281 mm.Hg%]) than in pEF-LVNC (1730 [1368–1691 mm.Hg%]) (p=0.001), while both LVNC groups were lower than control (2201 [1965–2406 mm.Hg%]) (pEF-LVNC p=0.001, rEF-LVNC p<0.0001). Global wasted work (GWW) was significantly lower in rEF-LVNC (204 [181–231 mm.Hg%]) than in pEF-LVNC (154 [115–171 mm.Hg%], p<0.0001) and control (61 [45–98 mm.Hg%], p<0.0001). Global work efficiency (GWE) was significantly lower in rEF-LVNC (18.3 [15.4–19.6%], p=0.001 than in pEF-LVNC and control. In both pEF-LVNC and rEF-LVNC, impaired GWE and GCS were the parameters most significantly associated with increased risk of cardiovascular events as detailed in Figure 2. Conclusion: MWA is a promising parameter for risk assessment of LVNC patients especially because it is less load-dependent and, unlike LVEF, incorporates left ventricular haemodynamics. Funding Acknowledgement: Type of funding source: Foundation. Main funding source(s): 2018 research grant from the Swiss Heart Foundation